Fauna of aquatic invertebrate water currents of National Park «Belo viez skaja Pustchia» - Moroz, Michail D.; Baitchorov, Vladimir M.; Giginiak, Juriyi G. (Experimental Biology and Biotechnology, 2018)
The aquatic invertebrate ten river ecosystems of National Park «Beloviezskaja Pustchia» were studied. 106 species of aquatic invertebrate belonging to 3 types: Mollusca – 27, Annelida – 7 and Arthropoda – 72 species were registered. The richest fauna of aquatic invertebrates has been presented in the rivers Nemerzhanka and Narevka. The big number of group of the types having reofilic properties is important ecological feature of the studied ecosystems and, obviously, specifies in general rather high quality of waters in the studied rivers. Nemoura cinerea (Retzius, 1783) was dominating species. Researches have allowed to reveal 22 species which weren’t registered that territories of National Park «Beloviezskaja Pustchia».